685 THE IMPACT OF ADJUVANT THERAPY ON SURVIVAL FOR NODE-NEGATIVE ESOPHAGEAL SQUAMOUS CELL CARCINOMA: A PROPENSITY SCORE MATCHED ANALYSIS. (17th September 2021) - Leng, Xue-feng; He, Wenwu; Jiang, Yingchun; Leng, Xuefeng; Luo, Qiyu; Mao, Tianqin; Zheng, Kai; Han, Yongtao
Abstract:  : At present, the primary treatment of esophageal cancer is surgery-based comprehensive treatment, including adjuvant therapy such as chemotherapy and/or radiotherapy. However, the role of adjuvant therapy for esophageal squamous cell carcinoma (ESCC) with pathologically node-negative (pN0) disease is controversial. This study aimed to evaluate the impact of postoperative adjuvant therapy on survival in patients with pN0 ESCC. Methods: Patients with ESCC who underwent R0 esophagectomy in the Department of Thoracic Surgery of Sichuan Cancer Hospital from Jan. 2008 to Dec. 2013 were involved. Patients were divided into two groups: surgery alone (Group S) or surgery + adjuvant therapy (Group S + A). The primary outcomes were overall survival (OS) and disease-free survival (DFS) between the two groups, and every consecutive case was followed up to death or the last follow-up. Results: The study involved 387 patients with pN0 ESCC. After propensity score matching, each group consisted of 150 patients. In the overall cohort, the 5-year OS (p = 0.004) and 5-year DFS (p = 0.003) rates were higher in Group S + A than in Group S. In matched samples, the same outcomes were observed (5-year OS: p = 0.026; 5-year DFS: p = 0.014). Postoperative chemotherapy was associated with longer OS (p = 0.02) and DFS (p = 0.004); T3 tumors (p = 0.004) and < 15 lymph node dissections (p = 0.002) were independent risk factors for pN0 ESCC. Conclusion: As the study revealed, adjuvant therapy, especially chemotherapy, prolonged OS and DFS for patients with ESCC who had pN0 disease. Fewer lymph node dissections and T3 stage tumors were independent risk factors for OS and DFS.